TEACHING TECHNOLOGIES FOR ENGLISH VOCABULARY TO SCHOOL STUDENTS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The acquisition of vocabulary is a fundamental aspect of learning a new language, and English is no exception. With the increasing role of technology in education, various modern teaching technologies have been introduced to enhance vocabulary learning for school students. This article explores a variety of digital tools, including language-learning apps, interactive platforms, multimedia resources, and gamification techniques, that can significantly improve students’ vocabulary retention. These technologies provide a dynamic and engaging environment for learning, making vocabulary acquisition more effective and enjoyable. By incorporating tools such as Quizlet, Duolingo, Memrise, and VR/AR, educators can tailor learning experiences to meet students’ individual needs, thereby fostering better understanding and use of the English language.